Law of Torts in the West Indies: cases and commentary - Kodilinye, Gilbert (Faculty of Law Library U.W.I. Cave HillBB, 1992)
Presents actual case-law reports of reported and unreported decisions decided by courts in particular Commonwealth Caribbean jurisdictions viz. Antigua, The Bahamas, Barbados, Dominica, Grenada, Jamaica, St. Lucia and Trinidad and Tobago.